Low‐Grade Myelodysplastic Syndromes with Preserved CD34+ B‐Cell Precursors (CD34+ Hematogones). Issue 1 (18th June 2019) - Chen, Zhining; Ok, Chi Young; Wang, Wei; Goswami, Maitrayee; Tang, Guilin; Routbort, Mark; Jorgensen, Jeffrey L.; Medeiros, L. Jeffrey; Wang, Sa A.
Abstract : B‐cell progenitors (hematogones) are markedly decreased or completely absent in the bone marrows of myelodysplastic syndromes (MDS), and the finding is considered as an important feature in MDS flow cytometry immunophenotyping. We studied CD34+ hematogones as a proportion of total CD34+ cells in 160 treatment naïve low grade primary MDS patients, consecutively collected over a two‐year period. While confirming that the median CD34 + hematogones was significantly decreased (1.08%, 0%, to 67.86%), we observed variably preserved CD34 + hematogones in some MDS patients. Using a 5% cutoff, a total of 46 (29%) MDS patients had ≥5% CD34 + hematogones, significantly overrepresented by MDS with ring sideroblasts (RS) (MDS‐RS) (18/40, 45%, vs. 28/120, 23%, P = 0.015). While we did not observe unique features among MDS‐RS, mutations were noticeably absent in a significant number of MDS without RS (37% vs. 14%, P = 0.013), including TP53 mutations (0% vs.16.5%, P = 0.021) if ≥5% CD34 + hematogones were present. Although the follow up was short (18.5 months, 0 to 151.0), a better overall survival was observed in MDS with ≥5% CD34 + hematogones, either as a group ( P = 0.008) or among patients with no RS ( P = 0.028). In multivariate analysis, reduced hematogones remained to be significant hazard ( P = 0.015). In summary, preserved CD34 + hematogones (≥5%) are seen in over a quarter of primary low‐grade MDS and these cases are overrepresented by MDS with RS or MDS with no detectable mutations. The finding is new, and this phenomenon may in part attribute to preservation of B‐cell differentiation of CD34+ progenitors, and it is associated with a better prognosis in low grade MDS patients. © 2019 International Clinical Cytometry Society